Excited state evolution of DNA stacked adenines resolved at the CASPT2//CASSCF/Amber level: from the bright to the excimer state and back1. Issue 11 (21st March 2015) - Conti, Irene; Nenov, Artur; Höfinger, Siegfried; Flavio Altavilla, Salvatore; Rivalta, Ivan; Dumont, Elise; Orlandi, Giorgio; Garavelli, Marco
<x xml:space="preserve">Abstract</x> La and excimer state population exchange, along the common puckering decay coordinate, explains the longest DNA lifetime component.